Impact of Polymorphism of CYP2D6 on Equilibrium Concentration of Duloxetine in Patients Suffering from Major Depressive Disorder - Zastrozhin (Psychopharmacol Bull, 2020)
INTRODUCTION: Duloxetine is commonly prescribed to patients with recurrent depressive disorder. Some part of patients in this group do not respond adequately to treatment regimen containing duloxetine, while many of them experience dose-dependent adverse drug reactions. Previous research investigated that CYP2D6 is involved in the biotransformation of duloxetine, the activity of which is highly dependent on the polymorphism of the gene encoding it. OBJECTIVE: The objective of this study was to evaluate the influence of 1846G > A polymorphism of the CYP2D6 gene on the concentration/dose indicator of duloxetine, using findings on enzymatic activity of CYP2D6 (as evaluated by the 6M-THBC/pinoline ratio measurement) and on CYP2D6 expression level obtained by measuring the hsa-miR-370-3p plasma concentration levels in patients suffering from recurrent depressive disorder. MATERIAL AND METHODS: This study enrolled 118 patients with recurrent depressive disorder (average age – 40.6±17.1 years). Therapy included duloxetine in an average daily dose of 103.7±37.1 mg per day. Treatment efficacy was assessed using the international psychometric scales. Therapy safety was assessed using the UKU Side-Effect Rating Scale. For genotyping we performed the real-time polymerase chain reaction (PCR Real-time). Therapeutic drug monitoring has been performed using HPLC-MS/MS. RESULTS: Our findings revealed the statistically significant results in terms of the treatment efficacy evaluation (HAMD scores at the end of the treatment course): (GG) 9.0 [7.0; 10.0] and (GA) 11.0 [8.5; 14.0], p < 0.001; at the same time, the statistical significance in the safety profile was obtained (the UKU scores): (GG) 3.0 [3.0; 4.0] and (GA) 4.0 [3.0; 4.0], p = 0.007. We revealed a statistical significance for concentration/dose indicator of duloxetine in patients with different genotypes: (GG) 0.776 [0.529; 1.067] and (GA) 1.388 [0.942; 1.732], p < 0.001. CONCLUSION: Thus, the effect of genetic polymorphism of the CYP2D6 gene on the efficacy and safety profiles of duloxetine was demonstrated in a group of 118 patients with recurrent depressive disorder.